2019
DOI: 10.1093/pm/pnz250
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Abuse and Route of Administration of Extended-Release Tapentadol Among Treatment-Seeking Individuals, as Captured by the Addiction Severity Index–Multimedia Version (ASI-MV)

Abstract: Background Tapentadol is a molecule incorporating mu opioid receptor agonism and norepinephrine reuptake inhibition to provide analgesia, with the potential for a lower incidence of gastrointestinal side effects than full mu opioid agonists. Postmarketing surveillance of tapentadol as an active pharmaceutical ingredient has consistently revealed low levels of abuse and diversion. Objective The purpose of the present study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
(39 reference statements)
0
9
0
1
Order By: Relevance
“…This practice could have potential patient safety implications with accidental overdose and misuse. On the other hand, several US and Australian studies showed that both tapentadol IR and extended release (ER) might have lower abuse liability in the community than oxycodone 33–35 . Hence, use of a lower abuse liability drug in the hospital setting could potentially reduce the risk of chronic use but care needs to be taken on the choice of opioid upon hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This practice could have potential patient safety implications with accidental overdose and misuse. On the other hand, several US and Australian studies showed that both tapentadol IR and extended release (ER) might have lower abuse liability in the community than oxycodone 33–35 . Hence, use of a lower abuse liability drug in the hospital setting could potentially reduce the risk of chronic use but care needs to be taken on the choice of opioid upon hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several US and Australian studies showed that both tapentadol IR and extended release (ER) might have lower abuse liability in the community than oxycodone. [33][34][35] Hence, use of a lower abuse liability drug in the hospital setting could potentially reduce the risk of chronic use but care needs to be taken on the choice of opioid upon hospital discharge. Finally, initiatives to reduce inappropriate prescription, including prescriber education regarding the risks of prescribing SR opioids for acute pain should be encouraged.…”
Section: Pattern Of Tapentadol Prescribingmentioning
confidence: 99%
“…The modest number of participants may be because of the market share of tapentadol, but it may also be because of the nondesirability of tapentadol for NMU. This may be a topic for future research [ 8 ]. Extension of the recruitment period longer than 5 months might result in a larger sample size, if the reason for the modest sample is the lack of tapentadol market penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the prevalence of tapentadol abuse and diversion (both ER and IR) has been characterized as low compared with other prescription opioid compounds, particularly when considered at the population level [ 6 - 8 ]. For instance, from the fourth quarter of 2011 to the second quarter of 2016, tapentadol had an event rate of 0.015 for intentional abuse, an event rate of 0.029 for diversion, and an event rate of 0.245 for past 30-day use to get high.…”
Section: Introductionmentioning
confidence: 99%
“…Data sources that capture actual use and drug-related behaviors, including the Addiction Severity Index-Multimedia Version (ASI-MV ® , Inflexxion, a division of Integrated Behavioral Health, Irvin, CA, USA), may provide more accurate insights into nonmedical use (NMU) of prescription opioid medications. ASI-MV data have been previously used to evaluate NMU prevalence of specific opioid products or compounds [14][15][16] and effectiveness of interventions such as abuse deterrent formulations [17].…”
Section: Introductionmentioning
confidence: 99%